2014
DOI: 10.1128/aac.02139-13
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pharmacokinetics of Piperacillin and Tazobactam Using Plasma and Dried Blood Spots from Infants

Abstract: f Piperacillin-tazobactam is often given to infants with severe infection in spite of limited pharmacokinetics (PK) data. We evaluated piperacillin-tazobactam PK in premature and term infants of ages <61 days with suspected systemic infection. Infants received intravenous piperacillin-tazobactam (80 to 100 mg/kg of body weight every 8 h [q 8 h]) based on gestational and postnatal age. Sparse plasma samples were obtained after first and multiple doses. Drug concentrations were measured by tandem mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 29 publications
1
62
1
3
Order By: Relevance
“…[8][9][10] To date, the pharmacokinetics of piperacillin/tazobactam have been described in (pre)term neonates and non-ICU children, but only in a small number of children admitted to the paediatric ICU (n=13 and n=12 patients), between 1 and 9 years of age. 7,[11][12][13][14][15] Any effort to define the dose rationale in infants and young children needs to account for the effect of developmental processes, which are known to affect drug exposure and potentially treatment response. 16 Moreover, the impact of pathophysiological changes on pharmacokinetics has been widely demonstrated in critically ill adults.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] To date, the pharmacokinetics of piperacillin/tazobactam have been described in (pre)term neonates and non-ICU children, but only in a small number of children admitted to the paediatric ICU (n=13 and n=12 patients), between 1 and 9 years of age. 7,[11][12][13][14][15] Any effort to define the dose rationale in infants and young children needs to account for the effect of developmental processes, which are known to affect drug exposure and potentially treatment response. 16 Moreover, the impact of pathophysiological changes on pharmacokinetics has been widely demonstrated in critically ill adults.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacodynamic predictors of efficacy (e.g., T MIC ) for antibiotics do not change from the adult to the child. While evaluations of TZP pharmacokinetics in children are available, there are currently no published pharmacokinetic and pharmacodynamic data from children receiving extended-infusion TZP to guide optimal dosing on the basis of attainment of the target T MIC (14,15,(20)(21)(22)(23)(24)(25)(26)(27)(28). In addition, data regarding the population pharmacokinetics of tazobactam in children are limited (27,28).…”
mentioning
confidence: 99%
“…We found one method that measured ertapenem from dried blood spots for TDM in neonates, in whom sampling of larger volumes is not practical, and two that measured piperacillin/tazobactam [39,50,65]. However, it must be noted that using this sampling strategy it is not possible to determine free concentrations, which may be a problem for highly protein-bound drugs such as ertapenem (ca.…”
Section: Resultsmentioning
confidence: 99%
“…A bridging study has been performed for piperacillin and tazobactam and found concentrations in dried blood spots to be on average 62% and 52% lower compared with plasma, suggesting that piperacillin and tazobactam do not partition into red blood cells. A large range in the dried blood spot-to-plasma ratios was observed [65]. Moreover, one of the biggest potential advantages of dried blood spots, namely stability, has been shown to be insufficient to allow for transportation at room temperature [50].…”
Section: Resultsmentioning
confidence: 99%